WILD SOUR CHERRY SPECIES OF THE CAUCASUS, CENTRAL ASIA AND THE FAR EAST AND THEIR USE IN BREEDING - A. A. Yushev; Yu. S. Orlova (Труды по прикладной ботанике, генетике и селекции)
Expedition activities of VIR and its experiment stations greatly broadened the collected diversity of stone fruits with valuable plant material that can be used in breeding. Wild sour cherries from the Caucasus, Central Asia and the Far East introduced in the 1970–80s had a range of such important traits as immunity to fungal diseases, winter hardiness, drought resistance, restrained growth, vegetative reproduction ability, and were later used by Russian breeders for the development of new varieties and clonal rootstocks for growing cherries in various ecological and geographical areas of the country. The study of sour cherry samples collected in vivo helped in some cases to clarify some questions related to the range of polymorphism, taxonomic discrepancies, and the number of sour cherry varieties (Cerasus spp.) of Microcerasus prostrata (Labill.) Roem., Microcerasus incana (Pall.) Roem. and others. In general, this work contributed to the revision of the genus Cerasus Mill. by reducing the number of species in it, eliminating the extensive synonymy and the misidentified taxa. The breeding work aimed at creating new varieties and rootstocks for stone fruit crops is carried out in Russia at 4–5 institutions and employs wild species with important traits as source material. The future of effective breeding of resistant sour cherry varieties is impossible without the involvement of wild species with important breeding characteristics.